THE ROLE OF PRODUCTIVE FINANCING ON THE ECONOMIC WELFARE OF MEMBERS IN THE MAQASHID SHARIA (EAST JAVA ABA SHARIA COOPERATIVE) - Nur Shadrina Nadhilah; Tika Widiastuti (Universitas Airlangga, 2020)
The purpose of this study is to find out and analyze the role of productive financing of East Java ABA Sharia cooperative in delivering economic welfare to their member based on Maqashid Sharia. The research method used is a descriptive qualitative approach with a type of case study research. This study has some units of analysis which are productive financing of East Java ABA Sharia cooperatives and welfare enhancement of financed members. The Data processing techniques used are data reduction methods, data presentation, conclusions and verification. The results of the study will be described descriptively and accompanied by tables. The results of the study can be concluded that the financing of the East Java ABA Sharia cooperative plays a role in improving the welfare of members even though there are differences in the increase in welfare felt by each member. Welfare is measured by using the indicators of the maintenance of the five basic needs under the Maqashid Sharia, namely maintenance of religion, the soul, the mind, the descendant, and the wealth. Some members experience an increase in the maintenance of the five elements of these needs at once and some members only maintain a few elements of the needs that have increased. Generally, members experience an increase in well-being that only occurs in some elements of necessity maintenance.Keywords: Financing, Sharia Cooperatives, Welfare, and Maqashid ShariaREFFERENCE Kuncoro, Mudrajat. (2006). Ekonomi pembangunan: teori, masalah dan kebijakan. Yogyakarta: UPP STIM YKPN.Solihin, Ahmad Ifham. (2010). Pedoman umum lembaga keuangan syariah. Jakarta: Kompas Gramedia. Subagyo, Ahmad. (2015). Keuangan mikro syariah. Jakarta: Mitra wacana media. Said Saad Marathon. (2014). Ekonomi Islam, Cetakan kedua. Jakarta: Zikrul Hakim.Amin Widjaja Tunggal. (1995). Akuntansi untuk koperasi. Cetakan pertama. Jakarta: PT Rineka Cipta.Rujito. (2003). Pengenasan Kemiskinan. Jurnal Ekonomi Rakyat No.1 Maret 2003. Yogyakarta: Bank Rakyat Indonesia. Buchori, Nur Syamsudin. (2012). Koperasi syariah: teori & praktek. Tangerang: Pustaka Aufa Media (PAM Press). ———. Menteri Negara Koperasi Dan Usaha Kecil Dan Menengah Republik Indonesia. (2007). Peraturan Nomor: 35.3/Per/M.KUKM/X/2007. Tentang penilaian kesehatan Koperasi Jasa Keuangan Syariah (KJKS).———. Menteri Negara Koperasi Dan Usaha Kecil Dan Menengah. (2007). Peraturan Nomor: 35.2 /Per/M.KUKM/X/2007. Tentang pedoman standar operasional manajemen koperasi jasa keuangan syariah dan unit jasa keuangan syariah koperasi. ojk.go.idbps.go.id